OP21 Enhancing Capability: Patient Impact In Ultra-Orphan Conditions. (2019) - Tonkinson, Amanda; Livingstone, Heidi; Upadhyaya, Sheela; Leng, Gillian
Abstract : Introduction: Written evidence is submitted to the National Institute for Heath and Care Excellence (NICE) by patient organisations for all ultra-orphan evaluations. To enhance the capability of patient involvement at NICE and to further develop understanding of how patient generated evidence and input in ultra-orphan conditions can support the Health Technology Assessment (HTA) agencies beyond 2020, the Public Involvement Programme systematically reviews the impact the evidence has on committee decision making. Methods: This study captured data from September 2017 to August 2018 for seven ultra-orphan evaluations. A paper questionnaire was given to each committee member to complete for each evaluation and entered in to an online system for analysis. Findings were used to inform the committee views which were highlighted in feedback letters to the patient groups. The questions included: how much impact and what sort of impact the patients had; both qualitative and quantitative data; and, a specific question on clarification of quality of life data Results: We obtained 83 responses showing the submissions: had a moderately high or high impact; gave the committee particular insight into quality of life data not provided elsewhere; provided new evidence; interpret the data from other sources; and, demonstrated consistency with other sources Conclusions: Patient evidence is particularly useful for ultra-orphan conditions where other forms of evidence are limited. Patients can provide a unique insight into the burden of disease, the patient population, any updates of treatments and the impact on patient and carers. They provide real life data to the committee including information that standard Quality Adjusted Life Years measures do not. Evidence varied by condition with impact themes highlighting the effects on patient and carers including fear, stress and anxiety. The examples are recorded, updated annually and will be shared with national patient groups and offered internationally through the HTAi Interest Group on Patient and Citizen Involvement.